Peran Guru dalam Meningkatkan Minat Belajar Siswa pada Pembelajaran IPS di Sekolah Dasar - Al-Fathar Ihsan; Fairuz Afifah Kesogihin; Fanny Syahfitri; Nur Khalizah Tanjung; Roro Ayu Angeli; Eka Yusnaldi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Education is closely related to learning activities. In the entire educational process at school, learning activities are the most basic activities, which means that the success or failure of achieving educational goals depends on the learning process experienced by students as students in each school. In social studies learning, teachers are not only required to provide knowledge to students in mastering concepts related to social life and the environment. More than that, social studies teachers are expected to be able to equip students to make efforts to increase their knowledge. Therefore, thr role of teacher in improve social studies learning in elementary schools are very important to build an advanced generation in the future. he aim of this research is to increase students' interest in learning social studies in elementary schools. This research methodology uses a qualitative approach with the type of research being library research. The results of this research show that the teacher's role in increasing students' interest in learning in social studies subjects includes the use of media, organizing the class and stimulating to create an attitude of student participation in social studies subjects from all the teacher's roles above, that what they do is in accordance with the model participatory learning. There are several factors that support teachers when learning, including: the best possible and effective use of technology, good emotional condition of students, supportive environmental conditions, good quality teachers. And some of the inhibiting factors include a distance learning system that is less effective, technological constraints, namely slow internet network, poor emotional condition